2012
DOI: 10.2196/jmir.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Changing Landscape of Physician Quality Reporting: Analysis of Patients’ Online Ratings of Their Physicians Over a 5-Year Period

Abstract: BackgroundAmericans increasingly post and consult online physician rankings, yet we know little about this new phenomenon of public physician quality reporting. Physicians worry these rankings will become an outlet for disgruntled patients.ObjectiveTo describe trends in patients’ online ratings over time, across specialties, to identify what physician characteristics influence online ratings, and to examine how the value of ratings reflects physician quality.MethodsWe used data from RateMDs.com, which included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
374
1
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(402 citation statements)
references
References 14 publications
21
374
1
6
Order By: Relevance
“…33 Although physicians may believe that negative ratings outnumber positive ones on physician-rating Web sites, 34 numerous studies have found that not to be the case. 20,[35][36][37][38][39][40][41][42][43][44] This finding is consistent with what is known about consumer-sourced rating systems in general. In our study, parents reported posting positive ratings for physicians more often than negative ratings, by a factor of 3 to 1.…”
Section: -33supporting
confidence: 82%
See 2 more Smart Citations
“…33 Although physicians may believe that negative ratings outnumber positive ones on physician-rating Web sites, 34 numerous studies have found that not to be the case. 20,[35][36][37][38][39][40][41][42][43][44] This finding is consistent with what is known about consumer-sourced rating systems in general. In our study, parents reported posting positive ratings for physicians more often than negative ratings, by a factor of 3 to 1.…”
Section: -33supporting
confidence: 82%
“…38 This concern is prevalent for traditional (ie, not online) satisfaction surveys as well. 56 In fact, the bias may be most prominent among physicians who have the least number of satisfied patients.…”
Section: -33mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there is an increasing number of sites where users rate doctors. Several works have analyzed the content and scores of such reviews, mostly by manually examining a subset of them [4,5,6,7]. However, not much work has studied how to automatically classify doctor reviews.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has received the attention of many researchers, and several studies of the OHC have been conducted focusing on various issues, such as how online physician reviews have been used in different countries [2][3][4][5][6][7]; what are the differences between the traditional and online physician reviews [8]; and whether differences in medical specialty areas affect these reviews [5,9]. Nevertheless, in China, even though the OHC might help consumers look for a good physician, the queues at Chinese hospitals are legendary [10], which means that it is not easy to make an appointment with a physician.…”
Section: Introductionmentioning
confidence: 99%